Intraspecific variation in climate‐relevant traits in a tropical rainforest lizard. Issue Volume 22:Issue10(2016) (9th August 2016) - Llewelyn, John; Macdonald, Stewart L.; Hatcher, Amberlee; Moritz, Craig; Phillips, Ben L.
Abstract: Aim: The exceptionally rich biodiversity found in tropical rainforest is under threat from anthropogenic climate change. We recognize the threat, yet we have little knowledge of the capacity of tropical species to adjust their climate sensitivity in response to it. One indicator of a species' capacity to adjust to different climates is the amount of intraspecific variation observed in its climate‐relevant traits; if a climate‐relevant trait varies, and this variation is correlated with local climates, it suggests the species can adjust the trait to different conditions through either phenotypic plasticity or evolutionary adaptation. Here, we test for intraspecific variation in climate‐relevant traits in a rainforest specialist to shed light on the capacity of such species to adjust to different climates. Location: The Wet Tropics Bioregion, Australia. Methods: We studied 12 populations of a lizard that is a tropical rainforest specialist, the rainforest sunskink ( Lampropholis coggeri ), testing for intraspecific variation in four traits that are potentially important in determining a species' climate sensitivity. The measured traits were as follows: critical thermal minimum, critical thermal maximum, thermal optimum for sprinting, and desiccation rate. Results: We found substantial variation both through time and across space in the measured traits, suggesting both strong plasticity and substantial geographic variation. Moreover, trait variation was correlated with local climate variables, suggesting variation reflects adjustment to local conditions. Main conclusions: If physiological lability similar to that observed in rainforest sunskinks occurs in tropical rainforest species more generally, these taxa may not be as climatically specialized, and so not as vulnerable to climate change, as previously thought.